ENSINO E APRENDIZAGEM DE PORTUGUÊS COMO LÍNGUA DE ACOLHIMENTO (PLAC): SUBSÍDIOS PARA PRÁTICAS DOCENTES DIRECIONADAS: SUBSÍDIOS PARA PRÁTICAS DOCENTES DIRECIONADAS. - Isabella Saliba Pereira Chilante (Nepan editor, 2019)
Brazil, in recent years, has been reaching a large influx of immigrants, most of them coming from border countries facing social, economic and political crisis, in search of better living conditions. They face many challenges in the new country and language is one of them. In order to supply this need for efficient communication by immigrants, the concept of Portuguese as Host Language (PHL) was born. Considering that this is an emerging area in Brazil, we aim to provide in this article valuable information for assertive teaching practices by analyzing the linguistic profile of learner immigrants of PHL based on data collected in questionnaires, interviews and narrative. The re-sults suggest that the immigrant public has characteristics that differentiate them from learners of Portuguese as a foreign language, and the teacher in the PHL area should be aware of these specificities and prioritize activities that meet the needs of this public.